Distributed Systems for Data-Intensive Computing in Cloud Environments: A Review of Big Data Analytics and Data Management - Zeravan Arif; Subhi R. M. Zeebaree (AI Society & STMIK Indonesia, 2024)
Because of the increasing increase of data, which is frequently referred to as